Effectiveness of Buerger Allen Exercise and Warm Water Foot Soak on Foot Sensitivity Score in A Group of Patients with Type 2 DM - Asni Hasaini; Muhlisoh Muhlisoh; Martini Nur Sukmawaty (Indonesian Journal of Global Health Research, 2023)
Diabetes mellitus (DM) is a chronic metabolic disease that requires medical attention and self-care management, namely buerger allen exercise and warm water foot bath to avoid complications. One of the complications of DM is diabetic ulcer. The main cause of diabetic ulcers is due to reduced foot sensitivity. Objective to analyze the effectiveness of Buerger Allen exercise and warm water foot bath on foot sensitivity score. The research design is Quasi Experiment non equivalent prepost test and between two groups. In this study, 36 respondents were obtained through purposive sampling. The intervention was carried out for 6 consecutive days with implementation 2 times a day. The instrument used was a 10 gram monofilament tool. Analysis using paired t-test, independent t-test and ancova test. There is a mean difference before and after the intervention on foot sensitivity scores, but there is no significant difference between foot sensitivity scores performed buerger allen exercise with water foot soak (ρ value=0.447>0.05) and there is an influence of confounding variables, namely length of suffering (ρ value=0.000 <0.05). The both exercises can be used as an independent nursing intervention option as a preventive measure for peripheral blood circulation disorders of the feet.